Democratizing Local Legislation Through Public Participation: A Critical Analysis of Regulations in Central Sulawesi - Mohamad Safrin; Andi Reza Alief; Irzha Friskanov S (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2026)
This study critically examines the legal dimensions, mechanisms, and barriers to public participation in the formulation of local regulations (perda) in Central Sulawesi. Employing a socio-legal approach that integrates normative analysis with empirical inquiry, the research evaluates compliance with the 1945 Constitution, Law No. 12/2011 (amended by Law No. 15/2019), Law No. 23/2014, and Ministry of Home Affairs Regulation No. 80/2015. Empirical data were gathered through in-depth interviews with 45 informants, observations at 12 public consultation forums, and document analysis of three strategic local regulations across four regions during 2021–2023. The findings reveal a significant implementation gap: public participation has been reduced to procedural formality, fundamentally contradicting the principle of openness. Three critical legal deficits were identified: (1) the absence of legal sanctions for procedural participation violations; (2) insufficient clarity in mechanisms for substantively accommodating public input; and (3) the lack of a public right of action against regulations enacted without adequate participation. The study concludes that multidimensional legal reform, coupled with a community-based deliberative participation model, is essential to fostering authentic and equitable democratization within the local legislative process.